Exploring the Structure and Distribution of English Language -‘s in Genitive Case Phrases - Taci, Joana (Richtmann Publishing, 2012)
The purpose of this article is to discuss certain issues concerning the origin, development and assignment of English genitivecase. It is mostly focused on the ‘s possessive case constructions and their generation according to X’ theory. It is obvious that thereexist various explanations for the appearance and constant usage of the ‘s clitic. But as it is also stated in the article, one thing is for surethat such a possessive case marker originated from the OE case endings and as so it serves to prove the fact that OE used to be asynthetic rather than an analytical language. On the other hand, due to its structure characteristics (as being noun-main-nounconstructions where one (posses sum) modifies the other (possessor)) by which the pre-posed modified nouns serve as a determinerand as so such ‘s genitive phrases are generated under the DP projection.